Riverine pesticides in an agricultural catchment in northern Thailand: with focus on atrazine and metabolites - Lee, Theodora Hui Yian (2024)
This study investigates the longitudinal and temporal trends of atrazine, a persistent herbicide, in the Mae Sa catchment in northern Thailand. Concentrations of atrazine determined from targeted analysis were elevated during the wet season, and great variability was observed in relation to individual storm runoff hydrographs. When compared to regulatory limits, the observed atrazine concentrations in Mae Sa were generally below environmental thresholds of concern. However, greater risk may occur in other tributary systems feeding the Ping River, where some concentrations exceeding 2000 ng/L were observed, although they were not sustained for extended periods of time. Additionally, nontargeted screening identified 16 other agrochemicals with known potential environmental risks or associated toxicity. Despite the minor risk posed by atrazine alone, the research highlights the intricate interplay of agricultural practices, diverse pesticide application, and hydroclimatic factors in influencing pesticide dynamics. In the broader context, this study underscores the challenge of estimating risks arising from pesticide mixtures while using a combination of targeted analysis, nontargeted screening, in silico prediction models, and in vitro bioassays. Collectively, we find evidence of the presence of more than 100 pesticides in the catchment since dedicated work began there more than a decade ago.